A document-collection: study of the central african museum plaster collection of afro-brazilian museum-ufba- first research news (Cadernos de Sociomuseologia, 2017)
This post-doctoral research deals with the study of a collection of twelve copies of important works to act as a reference of the Center African Art, highlighted in the main specialized books and catalogs. Copies belong to the Afro-Brazilian Museum collection of the Federal University of Bahia (MAFRO / UFBA), were donated by the Royal Museum of Central Africa (Tervuren, Belgium). To understand the trajectory and the history of this collection of plaster copies, like collection-document, we had to work with institutional and personal stories, and live with lacunars spaces of the various files. This museum plot refers to the background of the creation of the great ethnographic museums, since the trajectory of the copies does not dissociate the trajectory of their original. The original pieces were taken from the former Belgian Congo, with productions of people in the geographic regions of the Democratic Republic of Congo and the North East of Angola. The colonial-slavery history, with its institutions and characters, is intertwined with parts in different contexts, since the withdrawal of their places of origin, nullifying their functions and uses, processing in ethnographic collections and later in art collections, serving material support for the dissemination of racial and racist ideas of cultural and social inferiority of African people. It is intended, at the end of the study process, produce a written narrative with several voices (book and catalog) and a expographic narrative, which will deal with matters relating to the implications and intertwining of stories involving the original collection and prints, different individuals and institutions that are particularly marked by their identity characteristics.Keywords: art central African, memory, patrimony, museums.